Housing cooperatives alternative to housing problem in the current eonomic crisis - Etxezarreta, Aitziber; Merino, Santiago (REVESCO. Revista de Estudios Cooperativos, 2013)
Markets are not equitable providers of basic need goods and social rights and this also applies to the field of housing. In the Basque Autonomous Community, house prices have stopped rising after two decades and the current real estate crisis has resulted in a dramatic drop of privately provided housing. At the same time, austerity measures have seriously constricted public housing policies and the possibilities for public housing provision. In this paper, we therefore propose to reinforce the role of housing cooperatives as an alternative for publicly or privately provided housing. We present various models of such cooperatives in order to find ‘best practices’ that could be implemented in our local context.